1992
DOI: 10.1002/jmv.1890370410
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen particles of subtypes adw and adr, and compound subtype (adwr) in symptom‐free carriers in Japan

Abstract: Of sera from 1,878 Japanese blood donors who carried hepatitis B surface antigen (HBsAg), 420 were subtyped as adw (22.4%) and 1,443 as adr (76.8%); only 15 (0.8%) contained HBsAg of subtype ayw or ayr. Sera with HBsAg/adr had higher HBsAg titres than those with HBsAg/adw (geometric mean of haemagglutination titre: 10.1 +/- 2.4 vs. 9.7 +/- 2.4, p less than 0.01), and a higher prevalence of hepatitis B e antigen (24% vs. 13%, p less than 0.001). Carriers of HBsAg/adr progressively predominated over those of HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Therefore, we speculate that differences in the clinical characteristics of patients with HBV can not be explained by only the HBV genotype and that HBV subtype is also an important factor in determining clinical outcomes. In support of this, past reports demonstrated that subtype adr has a higher replicative activity than subtype adw [Kanagawa et al, 1992], and subtypes may affect the development of chronic liver disease through their relationship with HBeAg/antiHBe status [Shiina et al, 1991]. A recent study describes a correlation between genotype and the clinical course in cirrhotic patients with subtype adw [Tsubota et al, 2001].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Therefore, we speculate that differences in the clinical characteristics of patients with HBV can not be explained by only the HBV genotype and that HBV subtype is also an important factor in determining clinical outcomes. In support of this, past reports demonstrated that subtype adr has a higher replicative activity than subtype adw [Kanagawa et al, 1992], and subtypes may affect the development of chronic liver disease through their relationship with HBeAg/antiHBe status [Shiina et al, 1991]. A recent study describes a correlation between genotype and the clinical course in cirrhotic patients with subtype adw [Tsubota et al, 2001].…”
Section: Introductionmentioning
confidence: 75%
“…Similar to HBV genotype, the distribution of HBV subtype throughout the world is regionally specific [Courouce et al, 1983]. Furthermore, HBV subtype may affect the development of chronic liver disease through association with HBe Ag/anti-HBe status [Shiina et al, 1991] and may be associated with replicative activity of HBV [Kanagawa et al, 1992]. Therefore, we have investigated the relationship between HBV subtype and the clinical aspects of chronic HBV infection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As a result, the present serotyping method may not be sensitive enough to screen patients co-infected with different serotypes. On the other hand, several other reports have described compound serotypes, such as adwr or adywr in infected patients [30][31][32][33] . Further study is needed to determine whether patients with compound subtypes are co-infected with different genotypes.…”
Section: Discussionmentioning
confidence: 99%